SPEECH PERSONALITY: PSYCHOLINGUISTIC ASPECT (ON THE MATERIAL OF SPEECH BEHAVIOUR OF SHERLOCK HOLMES): Стаття - Kulish, Anastasiia (Studia Philologica, 2021)
The article discusses the speech personality of Sherlock Holmes in a psycholinguistic aspect. The aim of the article is to identify linguistic characteristics of speech behaviour of Sherlock Holmes. In order to achieve the aim there has been proposed the psychological classification of speech personality where personality can belong to a harmonious, conflict or impulsive psychotype. Determination of the psychotype of Sherlock Holmes was carried out by the following parameters: general attitude of the speech personality to the process of communication, role and status in communication, compliance with social norms during the conversation, coherence of the topic of conversation, intentions of the communicant. Analysis of the lexical and grammatical layers of Sherlock Holmes' speech gave grounds to classify the personality speech to a certain psychotype. Key words: speech personality, linguistic features, speech behaviour, communication, psycholinguistics, psychotype.